Essential ocean variables and high value biodiversity areas: Targets for the conservation of marine megafauna. (October 2020) - García-Barón, Isabel; Santos, M. Begoña; Saavedra, Camilo; Astarloa, Amaia; Valeiras, Julio; García Barcelona, Salvador; Louzao, Maite
Highlights: Physiographic and oceanographic descriptors were important drivers of megafauna abundance. Surface temperature and Chlorophyll- a were selected as essential ocean variables. High-value biodiversity areas (HVBAs) were located over the W and NW Spanish waters. HVBAs were temporal and spatially stable over the time-series. Abstract: Effective conservation and management measures are needed to face the unprecedented changes that marine ecosystems, and particularly marine megafauna, are suffering. These measures require the identification of high-value biodiversity areas (HVBAs) which in turn require the identification of the essential ocean variables (EOVs) that shape the environmental envelope of communities ( i.e. space defined by a set of environmental variables). The aim of this study was to delineate and characterise the HVBAs for the north and northwestern Spanish seabird and cetacean community taking advantage of the sightings collected during the annual PELACUS oceanographic survey (2007–2016). We used distance sampling methodology to analyse the species detectability based on environmental conditions. Then, we delimitated the HVBAs and identified the EOVs defining the environmental envelope of the community based on a spatio-temporal modelling approach using Generalized Additive Models. Overall, the main environmental variables driving species abundance were the sea surface temperature (SST), the distance to the shelf-break and the chlorophyll- a concentration (Chl-a). The SST and Chl-a were identified as dynamic EOVs due to their highest relative predictor importance, driving the environmental envelope and shaping areas of higher density. HVBAs were located mainly over the northwestern Spanish waters and decreased towards the inner Bay of Biscay remaining spatially stable over the study period. By identifying community-level HVBAs, we can understand the underlying ecological and oceanographic processes driving the spatio-temporal patterns of biological communities, such as those composed by seabirds and cetaceans. This information would identify conservation targets to assist the allocation of management resources. In addition, the location of HVBAs can help to fulfil the emergent need for sound spatial information to support the implementation of marine spatial planning.